In Vitro Efficacy of Silver Carbene Complexes, SCC1 and SCC22, Against Some Enteric Animal Pathogens - M Alsadwi, Akhil; MA Ibrahim, Mohamed; N Shah, Kush; L Cannon, Carolyn; A Byrd, James; Caldwell, Denise; Droleskey, Bob; A Bailey, Christopher (The Iraqi Journal of Veterinary Medicine, 2024)
Silver carbene complexes (SCCs), a group of novel silver-based compounds capable of gradually releasing silver ions, have shown significant antimicrobial activity against a wide range of bacterial pathogens mainly isolated from human cases. The antimicrobial activity against animal isolated pathogens has yet been done. The in vitro efficacy of two SCCs with different carrier molecules (SCC1 with a methylated caffeine backbone and SCC22 with a dichloroimidazolium backbone) was investigated against three important animal and human pathogen species. SCC1 and SCC22 exhibited bacteriostatic and bactericidal effects against multidrug resistant Salmonella Typhimurium (poultry isolate), E. coli 843 and E. coli 1568 (swine isolates), and the poultry field isolates Salmonella Heidelberg, Salmonella Enteritidis, and Salmonella Montevideo with MICs and MBCs ranged from 16-21 µM (6-8 µg/mL) and 16-32 µM (6-12 µg/mL), respectively. Clostridium perfringens type A was sensitive to both SCC1 and SCC22 with the MICs being 11 (4 µg/mL) and 21 µM (8 µg/mL), respectively. These values were comparable to the MICs and MBCs for silver acetate. The MBCs against C. perfringens was >85 µM for SCCs and >192 µM for silver acetate (>32 µg/mL for all compounds). Ten hours incubation of C. perfringens with 40 µg/mL of all three products showed down regulation of virulence genes plc and netB, suggesting viable cells and silver can modulate the virulence. Treating the C. perfringens with higher concentration (100 µg/mL) of each SCC for 10 hours inhibited more bacteria compared to the untreated bacterial cells, however, no differences in the ultrastructure of lysed bacteria were seen and this concentration might not induce viable but non-culturable (VBNC) state as suggested by transmission electron microscopy findings. SCCs showed a broad antimicrobial activity against all bacterial species tested including multidrug resistant pathogens. Both SCCs demonstrated inhibitory effect against the Gram-positive anaerobic C. perfringens type A which could have a high accumulation capacity for silver ion. These data suggest that SCCs may represent a novel class of broad-spectrumantimicrobial agents, which may be used to reduce the burden of pathogenic bacteria in the gastrointestinal tract of poultry.